Rejestry komunikacyjne w dziejach polszczyzny = Communication registers in the history of Polish language - Dubisz, Stanisław (1949- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The application of the "language register" theory to the interpretation of the history of Polish language allows to differentiate four basic public discourse variants and four corresponding types of communication registers: politic, religious, educational and civilization.
Keywords: rejestr językowy/komunikacyjny; dyskurs publiczny; odmiany komunikacyjno-stylowe języka; dzieje języka polskiego; communication/language register; public discourse; communication-stylistic language variants; history of Polish language